Pengaruh Penggunaan Metode Diskusi Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti Kelas VIII - R, Rahmi; Aminullah, Aminullah; Latif, Idrus (Universitas Negeri Makassar, 2024)
This research aims to find out how the discussion method is used and whether there are significant differences in student learning outcomes in the subjects of Islamic Religious Education and Character in class VIII of SMP Negeri 1 Patimpeng. This research uses quantitative research with a quasi-experimental method with a non-equivalent control group design. Research data was obtained by providing questionnaires and tests. The data analysis technique uses inferential tests with the Independent Sample T-Test method. The results of this research show that the discussion method is effective on the quality of learning of Islamic Religious Education and Character in class VIII students at SMP Negeri 1 Patimpeng. This can be seen from the results of the t-test using SPSS version 29 on the pre-test and post-test scores of student learning outcomes. It can be seen that the 2-tailed probability (significance) is 0.022 < 0.05, so there is a significant difference in the quality of learning after using the method. discussion. Therefore, the discussion method is effective for the quality of learning.